בין המקום הזה למקומות אחרים: הקולנוע האתיהחדש - גרץ, נורית (מכאן, 2017)
Using recent research on ethics and human right (among others, works by Alain Badiu, Simon Critchley, Agamben, Elsassear and new interpretations of Levinas' philosophy) Gertz explores several recently made Israel films (including Jellyfish, Year Zero, and Nuzhat al-Fuad) which reflect a search for alternative history by linking up to different cinematic aesthetics: that of contemporary American films and that of European art cinema rooted in the great works of the mid-twentieth century (e.g. the films of Fellini, Antonioni, Wenders, Godard, Bergman and so on). Gertz focuses on how those films - though their point of origin is the un ending strife between races, genders, nationalities, and ethnicities lacking a common base for dialogue - use mid-twentieth century European cinematic language in order to create an ethical time that leads from the narrow time of the individual towards a broader, transcendental, universal time, or as Levin as put it - the time of the Other.